Web system and sales management in technology companies (LACCEI, 2024)
The objective of this study was to know the relationship that exists between the web system and sales management in technology companies, through a systematic review between 2017 to 2022. Databases such as Scielo, Scopus, Ebsco and ScienceDirect were used for the study. The search for empirical studies in allowed the identification of 30 scientific articles directly related to the variables web system and sales management, the Prisma methodology was used and after applying the exclusion criteria through the process in a flowchart were purged 19 studies for being within the exclusion criteria. As a result, 11 scientific articles were obtained for the analysis of our research. It is concluded that the companies that have implemented a web system achieved better results in sales management improving their profitability this means that there is a significant relationship between the feasible ones because it has been found that the greater the investment in the use of these systems, the greater the sales management generating profitability. Keywords-- Web system, management, sales, profitability.